Effect of Corporate Fundamental and Macro Economic Factors on Share Prices in Indonesia Stock Exchange Market - Mulyanto Mulyanto; Riyanti Riyanti (International Journal of Business Economics (IJBE), 2020)
This paper aims to examine and analyze the influence of fundamental and macroeconomic factors on stock prices either partially or simultaneously. The research subjects focused on LQ45 Index companies listed on the Indonesia Stock Exchange. Secondary data of Indonesian stock market share prices covering between 2013-2019 were used. One Least Square was used to analyze the data. The sampling technique used is the purposive sampling method, the sample used is the LQ45 Index Company. The results shows fundamental factors include ROA, ROE, DER, EPS, and PER have a positive and significant effect on stock prices. and Inflation and interest rates have a negative and significant effect on stock prices. And simultaneously these variables have a significant and significant effect on stock prices. The study can provide a picture that stock price movements have a strong and clear influence on the company's fundamentals and are reflected in some of the ratios contained in the financial statements, as well as macroeconomic conditions.